2014
DOI: 10.1111/ijs.12397
|View full text |Cite
|
Sign up to set email alerts
|

Anemia on Admission Predicts Short- and Long-Term Outcomes in Patients with Acute Ischemic Stroke

Abstract: Anemia is common among AIS patients and is associated with cardiovascular comorbidities. Low hemoglobin status independently predicts short and long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
74
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 31 publications
5
74
2
Order By: Relevance
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
“…There were also 2 studies that did not state the design 21, 26. There was a high degree of diversity in geographic location, with cohorts from Germany,8, 19, 25 Switzerland,16, 20 the United States,18, 24 the People's Republic of China,2, 22 Canada,23, 28 India,6 Israel,10 the Republic of Korea,9 Denmark,21 Taiwan,17 the United Kingdom,26 and Poland 7. In addition, 2 studies were conducted across multiple countries 1, 27.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations